Sequestration of Polystyrene Microplastics by Jellyfish Mucus - Lengar, Živa; Klun, Katja; Dogsa, Iztok; Rotter, Ana; Stopar, David (Frontiers in Marine Science, 2021)
The worldwide microplastics pollution is a serious environmental and health problem that is currently not effectively mitigated. In this work we tested jellyfish mucus as a new bioflocculent material capable of sequestration of polystyrene microplastics in aqueous environments. Mucus material was collected from different jellyfish species and was used to trap fluorescently tagged polystyrene microspheres. The efficiency of removal was tested using varying concentrations of microplastics and mucus. The interaction between the microplastics and mucus was determined by viscosity measurements and confocal laser scanning microscopy. Different mucus preparation methods were also tested: freshly prepared, mechanically sheared, freeze-thawed, freeze-dried, and hydrolyzed mucus. The results demonstrate that jellyfish mucus can efficiently sequester polystyrene microplastics particles from the suspension. The fraction of the removed microplastics was highest with freshly prepared mucus and decreased with freeze-thawing and freeze-drying. The mucus ability to sequester microplastics was completely lost in the hydrolyzed mucus. The results imply that the intact jellyfish mucus has the potential to be used as a biopolymer capable of removing microplastics material.